The Effect of Addition Mushrooms Baglog Waste to Growth of Earthworm (Lumbricus rubellus) Populations - Zulhaida, Maria; Karnan, Karnan; Ilhamdi, Moh. Liwa (Jurnal Biologi Tropis, 2025)
The utilization of organic waste as a cultivation medium is a crucial step towards promoting sustainable agriculture and mitigating environmental impact. This study aims to evaluate the effect of adding mushroom baglog waste on the population growth of earthworms (Lumbricus rubellus), serving as supporting material in invertebrate zoology. This quantitative research, employing a true experimental method (True Experimental Research), was conducted for 60 days in the researcher's yard at Kebon Kopi Complex, Pejeruk Village, Ampenan District, Mataram City. The research design utilized a completely randomized design with five treatments and seven replications. The applied treatments included P0 (0% mushroom baglog waste), P1 (25% waste), P2 (50% waste), P3 (75% waste), and P4 (100% mushroom baglog waste). The observed parameters were the number and weight of earthworms. Research data were analyzed using the ANOVA test and the Least Significant Difference (LSD) test. The analysis results indicated that the addition of mushroom baglog waste significantly affected the earthworm population (P<0.05), suggesting that different proportions of mushroom baglog waste can increase both the number and weight of earthworms.